MODEL HIDROLOGI UNTUK ANALISIS PENGARUH PERUBAHAN TATA GUNA LAHAN TERHADAP POTENSI KETERSEDIAN AIR DI DAERAH ALIRAN SUNGAI ( DAS ) SIAK - Iqbal, Muhammad; Sutikno, Sigit; Sandhyavitri, Ari (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Land use change in Siak watershed (DAS Siak), Indonesia affected to cause fluctuation ofSiakwater river flows.In order to mange watershed strategies required a hydrological modelwhich to represent the hydrological cycle of the watershed. TheSoil Water Assessment Tools(SWAT) application was implemented to simulate scenarios forland use changes in the period of2002, 2007, and 2012 in Siak watershed. The research has yieldthe following resuts; the optimaldetermination coefficient (R2) of themodels were = 0.6 (>0.4), with Nash Suflicfe Efficiency(NSE) was 0.5 (0.35).The ground water reserves was calculated by comparing the ratio ofQmaximum and Qminimum during the period of 2002 to 2012. The ratio of ground waterreserves were presented as the following orderin 2002 was 10,725, in 2007 was 6,834andin 2012was respectively. The higher the Qmaxsimum / Qminimum ratiothe more critical ground waterreserved could be.Keywords: Land use change, SWAT model, ground water reserve.